2010
DOI: 10.1155/2010/521843
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Spectroscopic and Biological Aspects of O, N‐ Donor Schiff Base Ligand and its Cr(III), Co(II), Ni(II) and Cu(II) Complexes Synthesized through Green Chemical Approach

Abstract: The monofunctional bidentate Schiff base ligand (o-vanillin)p-chloroaniline and its four new complexes of chromium(III), cobalt(II), nickel(II) and copper(II) have been synthesized by classical thermal and microwave-irradiated techniques. All the new derivatives have been characterized by elemental analysis, molecular weight determinations, molar conductance measurements, UV-Vis, IR and NMR spectral studies. The IR spectral data suggest the involvement of phenolic oxygen after deprotonation and azomethine nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…This band shifted to lower frequencies of about 50 cm -1 in the metal complexes, suggesting coordination through the C=N of the benzothiazole ring. This is further supported by the emergence of bands around 485-482 cm -1 in the metal complexes assigned to M-N 22,23 . The bands at 1077, 1056 and 1056 cm -1 in the ligand, [Ce(SBC)2(H2O)2](SO4)2 and [Nd(SBC)2(H2O)2](NO3)3, respectively were assigned to the thiocarbonyl group 19 .…”
Section: Conductivity Measurementsmentioning
confidence: 60%
“…This band shifted to lower frequencies of about 50 cm -1 in the metal complexes, suggesting coordination through the C=N of the benzothiazole ring. This is further supported by the emergence of bands around 485-482 cm -1 in the metal complexes assigned to M-N 22,23 . The bands at 1077, 1056 and 1056 cm -1 in the ligand, [Ce(SBC)2(H2O)2](SO4)2 and [Nd(SBC)2(H2O)2](NO3)3, respectively were assigned to the thiocarbonyl group 19 .…”
Section: Conductivity Measurementsmentioning
confidence: 60%
“…The absence of bands around 10120-11605, 16062-16180 and 25210 -25575cm -1 assignable to, respectively are due to charge transfer transitions from ligand to Ni(II) ion [23][24][25]. The electronic spectrum of cobalt (II) oxidized to Co(III) complex a d 6 ion consists of three bands in the region 25000, 29851 and 38462 cm -1 .…”
Section: Uv-vis Data and Metal-ligand Mole Ratiomentioning
confidence: 99%
“…The complexation process increased as temperature increased for all the metal ions until at a maximum of about 35 o C. The increased complexation of the metal ions to the ligand at relatively high temperatures (between [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] o C) showed that the complexation process may be endothermic [33]. From table II, Gibb's free energy change values were found to be negative indicating the feasibility and spontaneity of the complexation.…”
Section: Thermodynamics Of Complexationmentioning
confidence: 99%
“…Kloramfenikol digunakan sebagai kontrol untuk penghambatan pertumbuhan mikroba. Hasil yang ditunjukkan dari pengujian aktivitas antibakteri adalah baik karena semakin besar konsentrasi senyawa Schiff base, maka semakin besar pula zona diameter hambatnya, hal ini menunjukkan bahwa senyawa tersebut memiliki aktivitas antibakteri yang baik dikarenakan senyawa Schiff base sebagai donor atom (O dan N), 9 sehingga gugus hidroksil meningkatkan aktivitas biologi. 3 Gugus C=N pada Schiff base dapat bersifat sebagai antibakteri di mana gugus amina (NH 2 ) mempunyai elektron bebas.…”
Section: Pendahuluanunclassified